Recovery of skeletal muscle contractility after high- and moderate-intensity strength exercise - Raastad, T.; Hallen, J. (European Journal of Applied Physiology, 2000)
To examine neuromuscular fatigue and recovery, ten male strength athletes [mean (SE) 27.5 (1.4) years] performed a moderate- and a high-intensity strength exercise protocol. In the high-intensity protocol, the load was 100% of the subject's three-repetition maximum (3-RM) for squats and front squats, and 100% of the subject's 6-RM for knee extensions. In the moderate-intensity protocol, the load was 70% of the high-intensity protocol, and both protocols lasted 90 min. The contractile properties of the leg extensor muscles were tested using isokinetic knee extensions, electrical stimulation, and squat jumps. Tests were done before exercise, 5-20 min after exercise, and frequently for 33 h after exercise. The decrements in knee extension performance were greater after the high-intensity protocol (12-14%), as compared to the moderate-intensity protocol (6-7%, P < 0.01). Similar decrements were seen in squat-jumping performance after the high-intensity protocol. Decrements in electrically evoked force were also greatest after the high-intensity protocol (P < 0.05), and were more pronounced at 20 Hz stimulation than at 50 Hz stimulation (P < 0.05). The recovery of performance showed a biphasic pattern, with a rapid recovery within the first 11 h after exercise, followed by a leveling off or a second drop in performance 11-22 h after exercise. All variables were back to baseline by 3 h after the moderate-intensity protocol, while all variables were back to baseline by 33 h after the 100% protocol. The role of structural changes (excitation-contraction coupling and contractile proteins) in the long-lasting performance decrements seen after the high-intensity protocol is discussed.